2018
DOI: 10.1097/yic.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Does initial use of benzodiazepines delay an adequate pharmacological treatment? A multicentre analysis in patients with psychotic and affective disorders

Abstract: It is established that delayed effective pharmacotherapy plays a significant role in the overall burden of psychiatric disorders, which are often treated with symptomatic drugs, that is benzodiazepines (BZDs), in relation to their rapid onset of action and safety, despite long-term side effects. We aimed to assess the influence of initial treatment with BZDs on the duration of untreated illness (DUI) and whether specific sociodemographic and clinical factors could influence the choice of BZDs as first treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…This finding indicates that, despite the guideline recommendations, BDZs continue to be widely prescribed as first treatment in PD, 29 even though existing evidence suggests that long-term BDZ prescription might delay proper treatment in patients with mood and anxiety disorders, including PD. 56,57 Finally, we compared latency to SSRI treatment with findings from previous studies and observed some significant differences. The longer DUI in the present study could reflect a longer latency to treatment in patients with PD, but may be influenced by the setting of our study: all participants were undergoing CBT treatment, and may have been more inclined to access a nonpharmacological intervention.…”
Section: Discussionmentioning
confidence: 96%
“…This finding indicates that, despite the guideline recommendations, BDZs continue to be widely prescribed as first treatment in PD, 29 even though existing evidence suggests that long-term BDZ prescription might delay proper treatment in patients with mood and anxiety disorders, including PD. 56,57 Finally, we compared latency to SSRI treatment with findings from previous studies and observed some significant differences. The longer DUI in the present study could reflect a longer latency to treatment in patients with PD, but may be influenced by the setting of our study: all participants were undergoing CBT treatment, and may have been more inclined to access a nonpharmacological intervention.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, the use of BZD often continues while the antidepressant does not, 41,44 increasing the duration of untreated illness. 45 A greater concern with medication availability and greater insomnia severity increased the chance of being diagnosed with dependence. However, this model had low discriminatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of BZD often continues while the antidepressant does not, 41 , 44 increasing the duration of untreated illness. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Anxiety symptoms may precede or co-occur with depressive and sub-syndromic hypomanic symptoms and are associated with future poor treatment response. Especially at the onset, anxious prodromes in patients at high risk of developing BD might be underestimated and often are treated exclusively with symptomatic drugs [16,79].…”
Section: Anxious Symptomsmentioning
confidence: 99%
“…Benzodiazepines (BZDs) provide fast relief in the reduction of comorbid anxiety and are approved by Canadian Network for Mood and Anxiety Treatments as symptomatic drugs in the short-term treatment in BD; however, the appropriateness of their use in at-risk patients for BD is debated. Two recent works [79,90] asserted that prolonged use of BZDs in at-risk populations may extend the duration of untreated illness up to four years, delaying the administration of an adequate psychopharmacological treatment and an appropriate medical follow-up. The risk of drug misuse and dependence in BD patients appears higher than in other patients.…”
Section: Benzodiazepinesmentioning
confidence: 99%